48.3k views
2 votes
6x-2(-3x-5)=154

What the answer

User Afrischke
by
7.2k points

1 Answer

5 votes

Answer:

x = 12

Explanation:

Simplifying

6x + -2(-3x + -5) = 154

Reorder the terms:

6x + -2(-5 + -3x) = 154

6x + (-5 * -2 + -3x * -2) = 154

6x + (10 + 6x) = 154

Reorder the terms:

10 + 6x + 6x = 154

Combine like terms: 6x + 6x = 12x

10 + 12x = 154

Solving

10 + 12x = 154

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.

10 + -10 + 12x = 154 + -10

Combine like terms: 10 + -10 = 0

0 + 12x = 154 + -10

12x = 154 + -10

Combine like terms: 154 + -10 = 144

12x = 144

Divide each side by '12'.

x = 12

Simplifying

x = 12

User Doomspork
by
6.3k points